The Role of Ecommerce Adoption in Influencing The Increasing Income of Small and Micro Enterprises (MSEs) During The Covid-19 Pandemic - Kusumatrisna, Adam Luthfi; Projo , Nucke Widowati Kusumo (Universitas Muhammadiyah Prof. DR HAMKA., 2024)
The COVID-19 pandemic has devastated the world economy, including Indonesia. Large-scale social restrictions as a consequence of preventing the spread of the COVID-19 virus have hampered the economy. Micro and small enterprises (MSEs) are the sectors most affected by the COVID-19 pandemic. On the other hand, the eCommerce survey showed that 24.20 percent of businesses claimed to have experienced an increase in income during the COVID-19 pandemic. This study aims to (1) find out the extent to which eCommerce adoption and income increased in MSEs during the COVID-19 pandemic; (2) looking for the effect of eCommerce adoption on MSEs on increasing MSE income during the COVID-19 pandemic; (3) knowing which items of eCommerce adoption have a significant effect on increasing MSE income; and (4) find out how big the opportunity to increase the income of each eCommerce adoption item compared to businesses that do not adopt eCommerce. This study uses descriptive analysis and binary logistic regression. The researched eCommerce adoption is seen from three dimensions, namely online sales media, training related to the use of information technology for digital marketing, and the speed of eCommerce adoption. All variables of eCommerce adoption that were studied using binary logistic regression proved to have a significant effect on increasing revenue. Of all eCommerce adoption items, eCommerce businesses that use instant messages as a sales medium, had the opportunity to experience an increase in revenue during the COVID-19 pandemic by 2.41 times compared to businesses that do not use instant messages.